2019
DOI: 10.1163/22941932-40190217
|View full text |Cite
|
Sign up to set email alerts
|

Climate signals from intra-annual wood density fluctuations in Abies durangensis

Abstract: Ongoing climate change is expected to alter forests by affecting forest productivity, with implications for the ecological functions of these systems. Despite its great dendrochronological potential, little research has been conducted into the use of wood density as a proxy for determining sensitivity to climate variability in Mexico. The response of Abies durangensis Martínez, in terms of wood density and growth ring width, to monthly climatic values (mean temperature, accumulated precipitation and the drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
4
1
0
Order By: Relevance
“…At the low-, mid-, and high-elevation distribution areas in both aspects, precipitation in the winter and early spring of the current growing season showed a significant positive correlation with the ring-width indices of A. jaliscana. The result is consistent with previous studies in subtropical Mexico, indicating that precipitation, particularly in the winter-spring season (driest period in this region), is the main climatic factor influencing radial growth in temperate-like environments [11][12][13]15]. In the Mediterranean basin, a similar response was reported for Abies borisii-regis and A. cephalonica in the dry season (late spring-summer) [4,46].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…At the low-, mid-, and high-elevation distribution areas in both aspects, precipitation in the winter and early spring of the current growing season showed a significant positive correlation with the ring-width indices of A. jaliscana. The result is consistent with previous studies in subtropical Mexico, indicating that precipitation, particularly in the winter-spring season (driest period in this region), is the main climatic factor influencing radial growth in temperate-like environments [11][12][13]15]. In the Mediterranean basin, a similar response was reported for Abies borisii-regis and A. cephalonica in the dry season (late spring-summer) [4,46].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, we found a negative correlation between the previous precipitation of July and September (the wettest months of the year in this region) and tree growth; this response could be related to saturated soils and a lack of oxygen for physiological processes, even though most of the rainfall is lost by runoff when the soil infiltration capacity is exceeded [8]. This response is consistent with what has been observed in other high-elevation forests in Mexico [8,47]; however, in other similar forests, such as those dominated by A. durangensis and A. religiosa, the correlation of the ring-width chronologies of these two species with the summer rain is not significant [15,20]. In the Mediterranean basin, a similar response was reported for Abies cephalonica, where the humid season (autumn-winter) showed a negative correlation with tree growth [46].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several studies carried out in the area have evaluated the responses to climatic conditions (González-Elizondo et al, 2005; González-Cásares, Pompa-García & Camarero, 2017; Pompa-García et al, 2017a), while others have used density for biometric purposes (González-Cásares, Yerena-Yamallel & Pompa-García, 2016; Pompa-García & Venegas-González, 2016). It has also been reported that the wood density of a species ( Abies durangensis ) that coexists with the species evaluated in the present study is more sensitive to temperature than the tree-ring width (González-Cásares, Pompa García & Venegas González, 2018). In this study, density was used to improve the estimation of carbon capture and its response to climate and thus facilitate a reliable and valuable comparative analysis to broaden the knowledge of the carbon accumulation in forest ecosystems.…”
Section: Discussionsupporting
confidence: 63%